Effects of age on loudness-dependent auditory ERPs in young autistic and typically-developing children. (18th June 2021) - Dwyer, Patrick; De Meo-Monteil, Rosanna; Saron, Clifford D.; Rivera, Susan M.
Abstract: Limited research has investigated the development of auditory ERPs in young children, and particularly how stimulus intensity may affect these auditory ERPs. Previous research has also yielded inconsistent findings regarding differences in the development of auditory ERPs in autism and typical development. Furthermore, stimulus intensity may be of particular interest in autism insofar as autistic people may have atypical experiences of sound intensity (e.g., hyperacusis). Therefore, the present study examined associations between age and ERPs evoked by tones of differing intensities (50, 60, 70, and 80 dB SPL) in a large sample of young children (2–5 years) with and without an autism diagnosis. Correlations between age and P1 latencies were examined, while cluster-based permutation testing was used to examine associations between age and neural response amplitudes, as well as group differences in amplitude, over all electrode sites in the longer time window of 1–350 ms. Older autistic participants had faster P1 latencies, but these effects only attained significance over the right hemisphere in response to soft 50 dB sounds. Autistic participants had slower P1 responses to 80 dB sounds over the right hemisphere. Over the scalp regions associated with the later N2 response, more negative response amplitudes (that is, larger N2 responses) were observed in typically-developing than autistic participants. Furthermore, continuous associations between response amplitudes and age suggested that older typically-developing participants exhibited stronger N2 responses to all intensities, though this effect may have at least in part reflected the absence of small positive voltage deflections in the N2 latency window. Age was associated with amplitudes of responses to 50 dB through 70 dB sounds in autism, but in contrast to Typical Development (TD), little evidence of relationships between age and amplitudes in the N2 latency window was found in autism in the 80 dB condition. Although caution should be exercised in interpretation due to the cross-sectional nature of this study, these findings suggest that developmental changes in auditory responses may differ across diagnostic groups in a manner that depends on perceived loudness and/or stimulus intensity. Highlights: Faster P1 to 50 dB tones over right hemisphere in older ASD participants. In TD participants, no association between P1 latency and age. Larger N2 to 60 through 80 dB sounds in TD than ASD participants. In ASD, unlike TD, no association between age and N2 amplitudes to 80 dB sounds.